Measurement of vector boson production cross sections and their ratios using pp collisions at √s=13.6 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Sauer, Christof; et al. (Physics letters, 2024)
Fiducial and total W± and Z boson cross sections, their ratios and the ratio of top-antitop-quark pair and W-boson fiducial cross sections are measured in proton-proton collisions at a centre-of-mass energy of s=13.6TeV, corresponding to an integrated luminosity of 29 fb−1 of data collected in 2022 by the ATLAS experiment at the Large Hadron Collider. The measured fiducial cross-section values for W+→ℓ+ν, W−→ℓ−ν¯, and Z→ℓ+ℓ− (ℓ=e or μ) boson productions are 4250±150pb, 3310±120pb, and 744±20pb, respectively, where the uncertainty is the total uncertainty, including that arising from the luminosity of about 2.2%. The measurements are in agreement with Standard-Model predictions calculated at next-to-next-to-leading-order in αs, next-to-next-to-leading logarithmic accuracy and next-to-leading-order electroweak accuracy.
The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S. M. Weber, M. Wessels, J. Zinsser [und 2879 weitere]
Online verfügbar: 17. Mai 2024
Gesehen am 07.07.2025